Knowledge regarding Arterio-Venous Fistula among Hemodialysis Patients in a Hospital of Rupandehi - Shrestha, Pragya; Bhujel, Sanjeeta; Shah, Santosh (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: An arteriovenous fistula (AVF) is a connection between an artery and a vein as an access for rapid blood flow for hemodialysis. The vascular access complications are the major causes for high morbidity and mortality among patients. MATERIAL AND METHODS: A descriptive cross-sectional study was conducted to find out the awareness regarding AVF among 70 hemodialysis patients of Universal College of Medical Sciences, Rupandehi. The purposive sampling method was used. The data was collected by semi-structured interview schedule. The total duration of the study was from August 12, 2018 to October 5, 2018. The data was analyzed by using descriptive and inferential statistics with SPSS software version 20.0. RESULTS: The study revealed that 58.57% of the respondents had high awareness regarding AVF, 54.28% answered 4-6 weeks as a maturation time for AVF, 12.90% answered at least three times of daily checking thrill, 95.71% answered to avoid to carry heavy items and to check blood pressure on AVF site and 24.28% answered at least 3-5 times as times of doing daily rubber ball exercise. CONCLUSION: Based on the study findings, it is concluded that the respondents have good knowledge on maturation time of AVF, avoiding sleep on AVF arm, wearing tight cloth and carrying heavy items. Respondents had low knowledge on checking thrill on AVF site as well as rubber ball exercise. Hence, it is needed to continue awareness program regarding AVF among hemodialysis patients.